Analysis and assessment of methanol production by integration of carbon capture and photocatalytic hydrogen production. (August 2016) - Almahdi, M.; Dincer, I.; Rosen, M.A.
Highlights: An integrated system for converting carbon dioxide to methanol is assessed. The system uses amine based carbon capture, photocatalytic water splitting for hydrogen production, and CO2 hydrogenation methanol synthesis. Energy and exergy analyses are used in the assessment. Parametric study are conducted to investigate how varying operating conditions affects the system performance. Abstract: An integrated system for converting carbon dioxide to methanol is proposed, and four of its main components (carbon capture absorber, carbon capture stripper, photoreactor, and methanol synthesis reactor) are analyzed thermodynamically, focusing on exergy destruction. The carbon capture unit provides carbon dioxide extracted from industrial flue gas while the photocatalysis unit produces hydrogen from visible light via photocatalytic water splitting. Both, carbon dioxide and hydrogen are supplied to a methanol synthesis reactor at a specific feed rate, temperature and pressure. The thermodynamic analysis shows that the largest exergy destruction rate occurs in the photoreactor (706 kW). The second largest exergy destruction rate occurs in the methanol synthesis reactor (24.7 kW), while the exergy destruction rates are smaller in the carbon capture stripper (23.5 kW) and absorber (17.9 kW).